New Trends in One-Dimensional Dynamics in honour of Welington de Melo on the occasion of his 70th Birthday IMPA 2016, Rio de Janeiro, Brazil, November 14-17 /: in honour of Welington de Melo on the occasion of his 70th Birthday IMPA 2016, Rio de Janeiro, Brazil, November 14-17. (2019) - Unknown
No abstract available